Berbagai Model Kepemimpinan Islam: Penelitian - Andina Nur Fadlila; Cipto Hartanto; Euis Farida; Purwo Septri Nugroho; Siswadi (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This research aims to explore various leadership models within the context of Islamic education, including transformational, transactional, situational, collaborative, and servant leadership models. The method employed is a literature review of various theories and contemporary research findings. The discussion results indicate that transformational leadership encourages cultural innovation, while transactional leadership focuses on operational efficiency through reward systems. Situational and collaborative models emphasize flexibility and collective decision-making. Specifically from an Islamic perspective, leadership is actualized through moral values such as discipline, patience, and perseverance, rooted in spiritual intelligence. Furthermore, servant leadership prioritizes staff empowerment and student well-being. The implementation of these models is proven to have a significant impact on increasing student motivation, teacher job satisfaction, and creating a conducive school environment. This article also highlights the strategic role of inclusive leadership, including women's leadership, in building a quality culture using a participatory approach. In conclusion, the success of Islamic educational leadership requires planned training strategies, regular evaluation, and the integration of spiritual values in every managerial practice to face modern educational challenges.